Smugglers, Poachers and Wreckers in Nineteenth-Century English Painting - Christiana Payne (Cahiers Victoriens et Edouardiens, 2005)
This paper looks at the representation, in art, of three groups of people whose activities in the countryside and on the coast aroused conflicting reactions: moralists saw them as a threat to the social order, but they were rarely regarded as criminal within their own communities, and their status depended on laws which many saw as unjust, or which were subject to change. Paintings of poachers were usually didactic in tone, representing the poacher as guilty and ashamed; the smuggler, however, was depicted in a much more positive light, as a heroic ‘free trader’; while wreckers were sometimes shown as poor people exercising their right to subsistence, sometimes as relics of a savage past, before the improvements brought about by lighthouses and lifeboats. J. M. W. Turner, David Wilkie, Edwin Landseer and Charles Napier Hemy are amongst the artists discussed.